Smuggling of migrants (Forum on crime and society, 2019)
This issue of the Forum focuses on wildlife crime. It contains articles by a range of researchers and academics with experience in the subject. Forum on Crime and Society presents policy-oriented articles on issues related to crime prevention and criminal justice, focusing on trends and practices in the field of criminal justice that are of special significance to the international community.